Uji Efektivitas Cangkang Keong Mas (Pomacea canaliculata L.) Sebagai Biosorben Dalam Menyerap Logam Berat Merkuri (Hg) - Risna Mauriza; Husnawati Yahya; T.M. Ashari T.M. Ashari (Jurnal Serambi Engineering, 2020)
Adsorbent is one of the effective solutions to reduce the Hg metal content. The golden snail is a pest for agricultural and contains high of calcium carbonate. However, calcium carbonate can be used as an adsorbent. This study aimed to examine the effectiveness of golden snail shell powder in absorbing Hg metal. This research is a quantitative study consisting of dependent variables and independent variables. The dependent variable involved a concentration of 10 ppm mercury, and 100 rpm stirring time speed while the independent variable included of variations in powder mass and stirring time. The mass of golden snail powder used those are 0 gr, 5 gr, 10 gr, 15 gr, and 20 gr with a variation of stirring time for 15 minutes and 30 minutes for each sample of Hg metals. Each Hg sample was used at a concentration of 10 ppm. The calculation results obtained that the effectiveness of golden snail shell powder in absorbing Hg 10 ppm was the mass of 20 grams of golden snail powder with a stirring time of 30 minutes that was equal to 99.87% with the result of a decrease in concentration of 10 ppm Hg to 0.01 Hg ppm.